Consumer Preferences for Potato Cultivars with Different Culinary Aptitudes: a Case Study from São Paulo - de Oliveira, Anny Clemente Santiago; de Araújo, Thaís Helena; Spers, Eduardo Eugênio; da Silva, Hermes Moretti Ribeiro [UNESP]; de Lima, Lilian Maluf (Springer Nature, 2020)
This study employs both qualitative and quantitative methods to investigate consumer preference for and knowledge about potato cultivars, including their culinary applications and attributes. This study’s aim is to determine factors influencing consumers’ preference and willingness-to-pay for potato cultivars. A focus group and the Affective Acceptance Test (sensory test) were used. The sample group consisted of 21 people between 18 and 57 years old, who self-identified as potato consumers. Participants’ preference and willingness-to-pay was evaluated for six potato cultivars, compared two by two according to their culinary aptitudes. It was found that participants were not knowledgeable about the attributes related to different potato cultivars. Additionally, it was found that, while non-traditional cultivars meet the participants’ expectations, their willingness to pay is highly sensitive to price relative to more traditional and familiar cultivars.
Keywords: Potato demand; Willingness-to-pay, consumer preference